The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1371/journal.pone.0001416
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Analysis of Ionotropic Glutamate Receptor Function in Neuronal Circuits of the Zebrafish Olfactory Bulb

Abstract: Although synaptic functions of ionotropic glutamate receptors in the olfactory bulb have been studied in vitro, their roles in pattern processing in the intact system remain controversial. We therefore examined the functions of ionotropic glutamate receptors during odor processing in the intact olfactory bulb of zebrafish using pharmacological manipulations. Odor responses of mitral cells and interneurons were recorded by electrophysiology and 2-photon Ca2+ imaging. The combined blockade of AMPA/kainate and NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…In Drosophila, gain control is achieved by a nonlinear transfer function at the first synapse in the olfactory pathway [10]. In the insect antennal lobe and in the olfactory bulb, the average output firing rate remains relatively stable even if the input intensity varies over a wide range, presumably as a consequence of distributed inhibitory feedback onto the output neurons [18][19][20]. Hence, gain control in the first olfactory processing center may equalize the output activity and thereby contribute to the orthogonalization of activity patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila, gain control is achieved by a nonlinear transfer function at the first synapse in the olfactory pathway [10]. In the insect antennal lobe and in the olfactory bulb, the average output firing rate remains relatively stable even if the input intensity varies over a wide range, presumably as a consequence of distributed inhibitory feedback onto the output neurons [18][19][20]. Hence, gain control in the first olfactory processing center may equalize the output activity and thereby contribute to the orthogonalization of activity patterns.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the approximate connectivity W (f f ′ ) a , which does not attempt to equalize the outputs, achieves considerably better orthogonalization than W (f f ) a . As is apparent from (20), its coupling strengths depend not only on the correlations between the channels but also on the input activity levels of the respective neurons. It would be interesting to see whether the performance of the network studied in [27] could be improved by implementing connectivity…”
Section: Discussionmentioning
confidence: 99%
“…Primary sensory neurons excite mitral cells through AMPA and kainic ionotropic glutamate receptors (Tabor and Friedrich, 2008); therefore, treatment with kainic acid is expected to induce neural activity in the olfactory bulb. Adult fish were anesthetized with 4% tricaine (ethyl 3-aminobenzoate methanesulfonate solution; Sigma-Aldrich; Westerfield, 2000) and placed on a damp sponge.…”
Section: Methodsmentioning
confidence: 99%
“…Schematic illustration of selected cell types and synaptic connections in the OB. Modified from [91].…”
Section: Computational Functions Of Neuronal Circuits and The Olfactomentioning
confidence: 99%